ANALISIS PERAMALAN PENJUALAN AIR MINUM DALAM KEMASAN DISTRIBUTOR AIR AMANAH DENGAN METODE NAÏVE BAYES - naufal, muhammad muhammad; Kamarudin, Kamarudin; Windarsyah, Windarsyah (Universitas Multi Data Palembang, 2025)
This study aims to assist the Amanah Water Distributor in efficiently managing its stock of bottled drinking water by applying the Naïve Bayes method. This method analyzes historical sales data from 2023 to 2024 to accurately forecast monthly stock requirements. The developed forecasting system provides restocking recommendations to prevent overstocking—which can increase storage costs—and understocking—which may lead to lost sales opportunities. With more accurate forecasting, the system is expected to improve operational efficiency, minimize the risk of loss, and support more effective decision-making to ensure the sustainability of the Amanah Water Distributor’s business operations.